A metabolomic approach to elucidate the inhibitory effects of baicalin in pulmonary fibrosis. (1st January 2021) - Chang, Hong; Meng, Hong-yu; Bai, Wan-fu; Meng, Qing-gang
Abstract: Context: Baicalin, a major flavonoid extracted from Scutellaria baicalensis Georgi (Lamiaceae), has been shown to exert therapeutic effects on pulmonary fibrosis (PF). Objective: To use serum metabolomics combined with biochemical and histopathological analyses to clarify anti-PF mechanisms of baicalin on metabolic pathways and the levels of potential biomarkers. Materials and methods: Forty male Sprague–Dawley rats were randomly divided into the control, PF model, prednisolone acetate-treated (4.2 mg/kg/day) and baicalin-treated (25 and 100 mg/kg/day) groups. A rat model of PF was established using a tracheal injection of bleomycin, and the respective drugs were administered intragastrically for 4 weeks. Histomorphology of lung tissue was examined after H&E and Masson's trichrome staining. Biochemical indicators including SOD, MDA and HYP were measured. Serum-metabonomic analysis based on UPLC-Q-TOF/MS was used to clarify the changes in potential biomarkers among different groups of PF rats. Results: Both doses of baicalin effectively alleviated bleomycin-induced pathological changes, and increased the levels of SOD (from 69.48 to 99.50 and 112.30, respectively), reduced the levels of MDA (from 10.91 to 5.0 and 7.53, respectively) and HYP (from 0.63 to 0.41 and 0.49, respectively). Forty-eight potential biomarkers associated with PF were identified. Meanwhile, the metabolic profiles and fluctuating metabolite levels were normalized or partially reversed after baicalin treatment. Furthermore, baicalin was found to improve PF potentially by the regulation of four key biomarkers involving taurine and hypotaurine metabolism, glutathione metabolism, and glycerophospholipid metabolism. Conclusions: These findings revealed the anti-fibrotic mechanisms of baicalin and it may be considered as an effective therapy for PF.